New formulation for the topside ionosphere and plasmasphere based on NeQuick - Prol, Fabricio dos Santos; Pignalberi, Alessio; Smirnov, Artem (EDP sciences, 2025)
The total electron content (TEC) affecting signal propagation of Global Navigation Satellite Systems (GNSS) is strongly influenced by the topside ionosphere and plasmasphere. This study introduces a new approach to representing the two regions. The developed topside ionosphere and plasmasphere model has been evaluated using TEC data from the COSMIC/FORMOSAT-3 mission, the Swarm-A satellite, and Global Ionospheric Maps (GIMs), covering the period from 2008 to 2024. Van Allen Probes data have also been used as a benchmark for the plasmasphere. All results have been obtained on the basis of a modified version of the NeQuick 2 model, named IonoMAP (Ionospheric Mapping). Although the new formulation for the topside ionosphere and plasmasphere still slightly underestimates TEC, it reduces biases to approximately 1–3 TECU and improves accuracy by 28–40% compared to the NeQuick 2 model formulation. These results suggest that the proposed model is a viable solution to improve current modeling of the topside ionosphere and plasmasphere.
Keywords: Topside Ionosphere; Plasmasphere; GNSS; VTEC; fi=Tietotekniikka tekn|en=Information Technology tech|